Genetic diversity of some apple cultivars in the south of Syria based on morphological characters - Al-Halabi, O.; Muzher, B. (International Journal of Environment, 2015)
This work was aimed to evaluate genetic diversity among five local and six introduced apple cultivars in the germplasm which located in the South of Syria based on 29 morphological characters of leaf and fruit. The analysis of variance showed significant differences at P < 0.05 for all measured parameters, however the mean values of Limb length and width, fruit weight, length, and width indicated to a wide range of diversity between local and introduced cultivars, that the introduced cultivars have mostly the highest mean value while the local cultivars have the lowest mean values, that clearly found in the local apple cultivar Ksairi (K) which revealed the lowest mean value of fruit weight (FW), fruit length (FL) and fruit diameter (FD) in the comparison with all studied cultivars. Likewise, principal component analysis (PCA) was used and the first 4 principal components accounted for 76.4% of the total variance, with eigen values 29.2%, 18.8%, 16.9% and 11.5% respectively. The main important characters in PC1 are correlated with the high mean value of width of stalk cavity (WP), fruit weight (FW), fruit diameter (FD), fruit length (FL), core length (CL), width of calyx cavity (WC), core width (CW), depth of stalk cavity (DP), stalk diameter (SD), seed width (SeW) and leaf margin (LM). PC2 discriminated among cultivars depending on Fruit shape (FS), leaf shape (LS), over color (OC), maturity time (MT), core shape (CS), limp length (LL) and leaf base (LB) which were able to differentiate between all studied cultivars . PC3 is correlated with the high mean value of Stalk length (SL), titratable acidity (TA), total sugar (TS), and total soluble solids (TSS). PC4 is correlated with the high mean value of depth of calyx cavity (DC), leaf apices (LA) and fruit cross section (FCS). Cluster analysis was also used that divided the studied cultivars into two clusters, the first cluster included all local apple cultivars, in addition to Leaz Golden (LG) cultivar, however AbouGhabra (AG) and Ksairi (K) cultivars revealed the highest similarity, which have the same fruit shape(FS), background color (BC), core shape (CS), fruit cross section (FCS), leaf shape (Ls) and leaf margin (LM). While the second cluster included all the other introduced cultivars. International Journal of Environment Vol.4(4) 2015: 86-99